Proses dan Langkah Penelitian Antropologi: Sebuah Literature Review - Askar Nur; Fakhira Yaumil Utami (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2022)
This study aims to explore the stages and research processes in anthropological studies. This research is a literature study that focuses on searching literature that is relevant to the research topic. The results of the research show that in anthropological research, there are stages and processes in the research including the field preparation stage. At the field preparation stage, things that must be prepared by researchers are research topics, understanding research ethics, research permits, determining informants, and initial observations at research sites so that researchers are able to understand the research location in detail.